Assessment of Physical and Solubility & Disintegration Properties of Zinc Cements Used for Operative Dentistry and the Comparison with the Standard - A. Zargar; R.Tabarak; MB. Tavakoli (Tehran University of Medical Sciences, 2005)
Statement of Problem: Zinc contained cements are so important among dental material as they have many indications and used in different ways therefore evaluation of their physical properties is so important in dentistry.Purpose: The purpose of this research was to measure some physical properties of zinc-contained cementsused in restorative dentistry. These cements included: Zinc oxide-eugenol, Zinc phosphate and Zinc polycarboxylate. Physical properties measured in this research were compressive strength, and setting timealso Solubility & Disintegration were evaluated.Materials and Methods: To perform this research two packs of each cement type were provided from an Iranian company products as prototypes and German HARVARD Dental GmbH company products as proofsamples. For compressive strength 11 samples provided from any type of cement. For setting time test, 16 samples provided from Zinc oxide-eugenol and 11 samples from two other types. For solubility &disintegration beet, 11 samples provided only from Zinc oxide-eugenol cement. The results compared with standard.Results: The results of Iranian product showed that compressive strength of Zinc oxide-eugenol- is I2.58±3 MPa, of Zinc phosphate cement is 37.2I±5.0 MPa and of Zinc polycarboxylate cement is 35.86±2.1 MPa.Setting time of Zinc oxide-eugenol cement is 2 9.04 ±0.7 1 min, of Zinc phosphate cement is 5.41 ±0.55 min and of Zinc polycarboxylate cement is 2.5±0.6 min. Solubility & disintegration of Zinc oxide-eugenol cement is 8.44±i.l%. None of these findings are in standard limit.Conclusion: By the use of standard charts it is concluded that: Only compressive strength of Zinc oxide-eugenol cement is between standard limits and compressive strengths of two other types of the cements are less than standard limits. Also only setting time -of Zincoxide eugenol cement is in standard limit and setting times of two other types of the cements aren't in standard limit. The German samples results were in standard limit. Solubility & disintegration-of Zinc-oxide eugenol cement isn't in standard limit. Therefore it is concluded that all types of these cements are not standard for use.